System Reliability Analysis of CRH380BL EMUs Pantograph - Yuanfei WANG; Hairong SUN; Chunxing PEI; Jie JIANG; Xiansheng LIU (机车电传动)
Based on the historical fault data of pantograph of CRH380BL EMUs, the fault distribution law of four main fault parts was studied by using the method of reliability data analysis, and then the reliability level of pantograph system was evaluated.ADD and air supply pipe, air supply pipe line, 10-X01 relay and pantograph airbag were the four parts that cause the most faults in pantograph. The results showed that the fault distribution of ADD, air supply pipe and 10-X01 relay is two-parameter Weibull distribution, and the fault distribution law of air supply pipe line and bow airbag is exponential distribution. Using the method of reliability analysis, the weak link of pantograph system reliability could be find out, which provided theoretical basis for EMUs fault overhaul and early warning.